2022
DOI: 10.1093/advances/nmac089
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Meat Factor in Animal-Source Foods on Micronutrient Absorption: A Scoping Review

Abstract: The EAT-Lancet Commission's planetary health guidelines suggest a reduction in the consumption of animal-source foods for better health and more sustainable food systems. Animal-source foods are highly nutrient-dense, therefore suited to address the widespread issue of micronutrient deficiencies, particularly in low-resource settings where diets are predominantly plant-based. Animal-source foods are also believed to contain the meat factor, a substance enhancing the absorption of micronutrients from plant-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…They contain high densities of micronutrients, particularly iron, zinc, and vitamins B6 and B12, which can be difficult to consume in sufficient quantities on a mostly vegetarian diet [82][83][84]. Molecules in animal tissue facilitate the absorption of micronutrients such as iron and zinc from both plant and animal foods in a meal, increasing the bioavailability of these nutrients [85,86]. The over-consumption of animal foods is associated with negative health outcomes and contributes to climate and environmental change [87,88].…”
Section: Wild Meat and Nutrition In Agroecological Landscapesmentioning
confidence: 99%
“…They contain high densities of micronutrients, particularly iron, zinc, and vitamins B6 and B12, which can be difficult to consume in sufficient quantities on a mostly vegetarian diet [82][83][84]. Molecules in animal tissue facilitate the absorption of micronutrients such as iron and zinc from both plant and animal foods in a meal, increasing the bioavailability of these nutrients [85,86]. The over-consumption of animal foods is associated with negative health outcomes and contributes to climate and environmental change [87,88].…”
Section: Wild Meat and Nutrition In Agroecological Landscapesmentioning
confidence: 99%
“…Hurrell et al (2006) reported that freeze-dried beef and chicken muscle increased iron absorption by 180% and 100%, respectively, relative to egg albumin, and suggested that the enhancing effect of muscle tissue on iron absorption was mainly protein related. A recent scoping review that systematically mapped studies on the meat factor (Consalez et al, 2022) concluded from data extracted from 77 eligible studies that the addition of muscle tissue and muscle tissue fractions to single plant-based meals steadily increased absorption of iron. There were no clear differences between red meat, poultry and fish in promoting the meat factor effect, and no evidence that milk and egg products contain the meat factor.…”
Section: Effect Of Meat On Non-haem Iron Absorptionmentioning
confidence: 99%
“…For example, foods rich in vitamin C along with non-heme iron sources can improve iron absorption. Meat, fish, and poultry contain factors that can enhance the absorption of both heme and non-heme iron (Basrowi andDilantika, 2021 andConsalez et al, 2022).…”
Section: Iron Absorption Uptake and Storagementioning
confidence: 99%